Worms, slugs and humans: the medical and popular construction of an emerging infectious disease Vermes, caramujos e humanos: as construções médica e popular de uma doença infecciosa emergente - Márcia Grisotti; Fernando Dias de Avila-Pires (História, Ciências, Saúde: Manguinhos)
The identification of the worm Angiostrongylus costaricensis parasitizing land snails and humans in Southern Brazil suggests under-diagnosis and under-notification of patients with abdominal angiostrongyliasis. This article analyzes how the concept of abdominal angiostrongyliasis was constructed in different ways in Costa Rica and Brazil and how these changes affected the understanding of its clinical and epidemiological diagnosis. The research shows that abdominal angiostrongyliasis is, de facto, a sociocultural construct, although the parasites and vectors are real. The analisys also shows the importance of an interdisciplinary approach for understanding disease. A identificação do verme Angiostrongylus costaricensis em humanos e caramujos, no sul do Brasil, sugere a ocorrência de subdiagnóstico e subnotificação de pacientes com angiostrongilíase abdominal. O artigo analisa as diferentes construções do conceito de angiostrongilíase abdominal na Costa Rica e no Brasil e a influência dessas variações em seu diagnóstico clínico e epidemiológico. Demonstra que a angiostrongilíase abdominal é, de facto, um constructo sociocultural, embora parasitas e vetores sejam reais. Também destaca a importância da abordagem interdisciplinar para a compreensão da doença.